Desktop VR Is Better Than Non-ambulatory HMD VR for Spatial Learning - Srivastava, Priyanka; Rimzhim, Anurag; Vijay, Palash; Singh, Shruti; Chandra, Sushil (Frontiers in Robotics and AI, 2019)
Use of virtual reality (VR) technology is proliferating for designing and upgrading entertainment devices, and creating virtual environments that could be used for research and training. VR is becoming a strong research tool by providing a tighter control on the experimental environment and by allowing almost limitless possibilities of creating ecologically valid stimuli. However, the enhanced fidelity between the real and virtual worlds that VR provides does not always benefit human performance. For a better understanding, and increasing VR’s usability, we need to identify the relevant constituent components of immersive technologies, and differentiate their roles, for example, how visual and interaction fidelity differentially improves human performance. We conducted an experiment to examine how two common VR display modes, head mounted display (HMD) and desktop (DT), would affect spatial learning when we restrict ambulatory locomotion in HMD. This manipulation allowed examining the role of varying visual fidelity with low interaction fidelity. We used a between-group design with 40 naïve participants. They explored a virtual environment and later drew its sketch-map. Our results showed participants spent more time and perceived less motion-sickness and task effort using desktop than HMD VR. With reduced interaction fidelity, the high visual fidelity of HMD as compared to desktop resulted in similar or poorer performance on different spatial learning tasks after accounting for motion-sickness and workload effort. Participants were better in recalling spatial components related to junction and cyclic order of the navigated virtual space in desktop versus HMD VR, and performed equally well on components related to street segments and object associations. We explain these results in terms of deficient idiothetic information in nonambulatory HMD and lesser sensory conflicts in desktop mode. Overall, our results highlight the differential effect of visual versus interaction fidelity on human performance based on using immersive technologies, how such an effect depends on the nature of cognitive and functional behavior users employ, and the higher usability of traditional desktop VR. These results are relevant for developing customized and sustainable virtual reality human-computer interactions.